2012
DOI: 10.1103/physrevlett.108.154502
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Free-Shercliff-Layer Instability in Cylindrical Geometry

Abstract: We report on observations of a free-Shercliff-layer instability in a Taylor-Couette experiment using a liquid metal over a wide range of Reynolds numbers, Re∼10(3)-10(6). The free Shercliff layer is formed by imposing a sufficiently strong axial magnetic field across a pair of differentially rotating axial end cap rings. This layer is destabilized by a hydrodynamic Kelvin-Helmholtz-type instability, characterized by velocity fluctuations in the r-θ plane. The instability appears with an Elsasser number above u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…In that respect, notions such as fast and slow waves [20], or Alfvénic MRI, are not relevant in the experimental context. Our analysis is in line with the conclusions of Gissinger et al [22] and Roach et al [23], who relate the modes observed in the Maryland and…”
Section: Discussionsupporting
confidence: 93%
“…In that respect, notions such as fast and slow waves [20], or Alfvénic MRI, are not relevant in the experimental context. Our analysis is in line with the conclusions of Gissinger et al [22] and Roach et al [23], who relate the modes observed in the Maryland and…”
Section: Discussionsupporting
confidence: 93%
“…Some experiments aimed at reproducing certain features of the accretion disks have focused on Taylor-Couette flows in water or liquid metal, both magnetized and unmagnetized, as the main experimental platform to study disk turbulence and MRI (Ji et al 2006;Roach et al 2012). Gas and plasma experiments are much less numerous and, generally, are not specifically conceived to study the physics of accretion disks (Ji 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Just as the Coriolis force causes rotating flows to become independent of the ordinate along the axis of rotation, so too can magnetic fields cause flows of electrically conducting fluid to become independent of the ordinate parallel to the direction of the applied field. Such free shear layers, now known as Shercliff layers 19 , have been studied both experimentally [20][21][22] , and numerically 19,[23][24][25] . Like their hydrodynamic cousins, these shear layers are unstable to a Kelvin-Helmholtz-type instability when the amount of shear becomes large relative to the restoring force.…”
Section: Introductionmentioning
confidence: 99%